Obstacle Avoidance System for Px4-Based Quadrotor in The Hardware in The Loop (HITL) Simulation of Simulink - Wilfred, Brian Jordan; Zakaria, Mohamad Fauzi (Evolution in Electrical and Electronic Engineering, 2025)
Unmanned Aerial Vehicles (UAVs) have become essential for various applications, with obstacle avoidance systems critical in ensuring safety and collision prevention in dynamic environments. Current testing methods often rely on real-world flight testing, which can be time-consuming, expensive, and risky for hardware. Thus, Hardware-in-the-loop (HITL) simulation provides a significant advantage by offering a safe, repeatable, and cost-effective virtual environment for testing and validating obstacle avoidance algorithms. This study aims to integrate a PX4-based autopilot system with a companion computer in MATLAB-Simulink and evaluate the effectiveness of an obstacle avoidance algorithm within a HITL simulation for a quadcopter. The proposed system integrates a 3D-VFH+ algorithm deployed on an Nvidia Jetson Nano for real-time obstacle avoidance, leveraging simulated sensor data and Unreal Engine for a realistic 3D environment. The results demonstrate that the system effectively navigates and avoids obstacles in dynamic scenarios with a parameter setting for a minimum distance to the obstacle at 0.3m.